Preliminary Evaluation of a Mobile, Web-Based Coaching Tool to Improve Pre-K Classroom Practices and Enhance Learning - Caroline Christopher; Sandra Jo Wilson; Mary Wagner Fuhs; Carolyn Layzer; Sophie Litschwartz (MDPI AG, 2023)
Educators rely on professional development to improve instruction. Research suggests that instructional coaching which utilizes specific coaching practices, such as classroom observation followed by debriefing and goal setting, and integrated strategies such as co-teaching, bring about significant change in instructional practices. The goal of this study was to gauge whether or not the use of a web-based data collection and coaching tool led to changes in focal classroom practices and whether or not improving those practices was, in turn, related to students' academic and self-regulation gains across the prekindergarten year. To examine the implementation and impact of the coaching app, researchers conducted a cluster-randomized trial, comparing the classroom practices of teachers receiving business-as-usual coaching to those being coached with the app. Classroom observation data showed no significant differences in teachers' practices across the school year, and student achievement did not differ between conditions. Qualitative data from coach interviews, however, revealed that coaches using the app were more likely to employ integrated coaching strategies associated with improving instruction. The lack of differences in terms of teachers' practices and students' assessment gains may be due to a lack of statistical power and inconsistent professional development implementation associated with ongoing disruptions due to the pandemic. Further research examining the effectiveness of educational technologies supporting professional development is needed.